PERAN LEMBAGA BANTUAN HUKUM BKBH UNRI DALAM MENGATASI PERMASALAHAN HUKUM MASYARAKAT DI DESA PULAU PERMAI - Hidayat, Tengku Arif; Putri, Riau Dela Islami; Dirgantara, Satrya; Indriani, Trifosa; Nainggolan, Tulus Malvin; Lovina, Angel Agnes; Amanda, Rindu Tesaniya; Anaqi, M. Fadillah Zaafa; Ulya, Raihannah; Ardelia, Dinda; Nasution, Nur Aini (Komunitas Manajemen Kompetitif, 2023)
Indonesia is a legal country that protects the rights of its citizens in the legal field. The form of embodiment of legal protection provided by the state to its citizens is Legal Aid. Legal Aid is a right that every citizen has which is guaranteed through the constitution, according to the 1945 Constitution of the Republic of Indonesia, Article 28D Paragraph (2). Legal aid is intended to assist the community in resolving the legal problems they face with the assistance of legal institutions or related parties who have the authority and obligation to provide legal assistance. The Pulau Permai Village Kukerta Team together with the legal aid agency BKBH (Legal Consultation and Assistance Agency) Faculty of Law, Riau University held an outreach to increase community knowledge regarding legal aid and the community's right to obtain legal aid. The public's lack of knowledge about legal aid has led the Kukerta team to carry out outreach activities containing material about legal aid, how to get legal aid, the conditions for getting legal aid and the forms of legal aid. The socialization activity also aims to resolve legal problems that the community has through direct discussions held with the present speakers. Regarding legal aid activities, these are regulated in Law Number 16 of 2011 concerning Legal Aid.